“We will write it again”: subverted hermeneutics in Tom Stoppard’s Arcadia - Aloysia Rousseau (Sillages Critiques)
Arcadia can be read as a subverted detective story in which history is reinterpreted rather than deciphered. The sleuth is a ruthlessly ambitious scholar who distorts evidence so as to achieve his ends. Arcadia thus highlights the unreliability of textual meaning, appealing to the reader/spectator’s vigilance and inviting him to participate in the hermeneutical quest. This paper will throw light upon the play’s double time frame as being characteristic of the whodunit before focusing on the figure of Bernard as anti-detective and finally analysing how visual deciphering prevails over scriptural deciphering.